Can Web-Based Environments Talk the Talk? - Wheeler, Matthew (Proceedings of the International Conference on Networked Learning, 2002)
This paper aims to discover what current student democracy / advocacy systems are prevalent within higher education institutions; focusing upon the communication between learners and their educators. The paper raises two questions; do the current democracy systems work (the learners perceptions)? And could a web-based environment assist the learners and educators to communicate in a more effective way? A case study of the operations within a new web-based environment (V-Rep) will be included as a comparison to the current systems. The study finds that web-based environments would be a useful addition to the current systems available within higher education institutions. The implications for the current systems are not great, as the web-based environment is aimed at enhancing communication between the learners and their educators, not to replace them.